2019
DOI: 10.1590/1678-4162-10063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seasonal conditions and milk management practices on bulk milk quality in Minas Gerais State - Brazil

Abstract: The influence of seasonality and the training and implementation of good dairy farming practices on raw milk production and quality was evaluated on dairy farms in Minas Gerais State, Brazil. The physico-chemical composition, somatic cell count (SCC) and total bacterial count (TBC) were determined in 3,096 milk samples collected from bulk tanks originated from 43 dairy farms over a three-year period and correlated with key climatic factors. The recommended milking management practices were applied through a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Rainfall substantially influences chemical composition, SCC, and TBC (Picinin et al 2019;Lima et al 2019). Based on this assertion, it is possible to understand such behavior regarding fat, protein, and DDE percentages.…”
Section: Discussionmentioning
confidence: 96%
“…Rainfall substantially influences chemical composition, SCC, and TBC (Picinin et al 2019;Lima et al 2019). Based on this assertion, it is possible to understand such behavior regarding fat, protein, and DDE percentages.…”
Section: Discussionmentioning
confidence: 96%
“…The significant increase in TBC in CG (33.7%) is believed to be related to the local rainy season (September to December), with rainfall of approximately 1,150 mm during this period according to the Brazilian National Institute of Meteorology (Inmet). Picinin et al (2019) observed an increase in the SCC and TBC parameters during a period with rainfalls and high temperatures (October to January), favoring an increase in environmental contamination, accumulation of mud in the facilities, and higher occurrence of dirty teats at milking time. These factors, associated with failures in the milking routine, may cause high initial contamination.…”
Section: Tablementioning
confidence: 89%
“…Regarding the CFU, it was observed that, in the rainy and dry seasons, 33.3 and 23.3%, respectively, of the farms presented values higher than 300.000 CFU/mL, which is the limit allowed for the quality bonuses payment for the production systems located in the studied region [ 24 ]. Other studies have reported higher total bacteria counts in tank milk samples during wet and rainy seasons, mainly attributed to the greater difficulty in handling animals with a high presence of sludge in the mammary gland and extremities during milking, and to the increases in the probability of making milk handling errors under these conditions [ 25 , 26 ]. Despite the observed variation in the CFU during the evaluated seasons, between 66.7 to 76.7% of the farms showed CFU values lower than 300.000 CFU/mL, which suggests that within the evaluated systems, the post-milking management does not imply a significant risk on the product sanitary quality, however, there are opportunities for improvement, so it is necessary to re-evaluate the methods of obtaining and storing the milk [ 19 ].…”
Section: Discussionmentioning
confidence: 99%